2016
DOI: 10.2217/nnm-2016-0316
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticles for Precision Oncology: Theranostic Magnetic Iron Oxide Nanoparticles for Image-Guided and Targeted Cancer Therapy

Abstract: Recent advances in the development of magnetic nanoparticles (MNPs) have shown promise in the development of new personalized therapeutic approaches for clinical management of cancer patients. The unique physicochemical properties of MNPs endow them with novel multifunctional capabilities for imaging, drug delivery and therapy, which are referred to as theranostics. To facilitate the translation of those theranostic MNPs into clinical applications, extensive efforts have been made on designing and improving bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
149
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(150 citation statements)
references
References 116 publications
1
149
0
Order By: Relevance
“…The studies revealed safe doses for administration (2.9 mg Fe per kg in humans), while it was previously demonstrated that NPs with 30 nm in size were uptaken by the macrophages in the spleen, liver, and lymph nodes . Magnetic‐iron‐based NPs thus will likely show lower safety concerns than other nanomaterials for the translational development of new theranostic agents for image‐guided and targeted cancer therapeutic approaches …”
Section: Magnetic Npsmentioning
confidence: 94%
“…The studies revealed safe doses for administration (2.9 mg Fe per kg in humans), while it was previously demonstrated that NPs with 30 nm in size were uptaken by the macrophages in the spleen, liver, and lymph nodes . Magnetic‐iron‐based NPs thus will likely show lower safety concerns than other nanomaterials for the translational development of new theranostic agents for image‐guided and targeted cancer therapeutic approaches …”
Section: Magnetic Npsmentioning
confidence: 94%
“…The technological progress regarding synthesis, characterization, biocompatibility and cytotoxicity of MNPs is evident, revealing positive advances in terms of quality, stability and applicability of these nano-sized platforms for imaging, diagnosis and treatment purposes. Despite the potential benefits of MNPs and their favourable outcomes for biomedical and theranostic applications, some fundamental points still require the researchers' attention [113].…”
Section: Future Challengesmentioning
confidence: 99%
“…Local retention of nanocomposites may prolong the half-life of the drug, enhance therapeutic efficacy, and reduce systemic adverse effects. [3][4][5] Application of a static magnetic field enhances MNP uptake by cultured cells, primarily by enhancing the sedimentation rate of MNPs. 6 The subsequent interaction between the cell and the NP is also important for cellular uptake, which may impact pharmacological efficacy.…”
Section: Introductionmentioning
confidence: 99%